Embryo Buoyancy and Cell Death Gene Expression During Embryogenesis of Yellow-Tail Kingfish Seriola lalandi - Palomino, Jaime; Gómez, Camila; Otarola, María Teresa; Dettleff, Phillip; Patiño-García, Daniel; Orellana, Renan; Moreno, Ricardo D. (Frontiers in Cell and Developmental Biology, 2021)
In pelagic fish, embryo buoyancy is a noteworthy aspect of the reproductive strategy, and is associated with overall quality, survival, and further developmental success. In captivity, the loss of buoyancy of early embryos correlates with high mortality that might be related to massive cell death. Therefore, the aim of this study was to evaluate under captivity conditions the expression of genes related to the apoptosis process during the early embryonic development of the pelagic fish Seriola lalandi, and its relationship to the buoyancy of embryos. The relative expression of bcl2, bax-like, casp9, casp8, and casp3 was evaluated by RT-qPCR and FasL/Fas protein levels by western blot in five development stages of embryos sorted as floating or low-floating. All genes examined were expressed in both floating and low-floating embryos up to 24 h of development. Expression of the pro-apoptotic factors bax, casp9, casp8, and casp3 was higher in low-floating as compared with floating embryos in a developmental stage-specific manner. In contrast, there was no difference in expression of bcl2 between floating and low-floating embryos. Fas protein was detected as a single band in floating embryos without changes in expression throughout development; however, in low-floating embryos, three higher intensity reactive bands were detected in the 24-h embryos. Interestingly, FasL was only detected at 24-h in floating embryos, whereas in low-floating samples this ligand was present at all stages, with a sharp increase as development progressed. Cell death, as evaluated by the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling assay, was highly increased in low-floating embryos as compared to floating embryos throughout all developmental stages, with the highest levels observed during the gastrula stage and at 24 h. The results of this study suggest that an increase in cell death, probably associated with the intrinsic and extrinsic apoptosis pathways, is present in low-floating embryos that might explain their lower developmental potential under captivity conditions.